Eye’ll persuade you: Exploring the use of eye contact among Filipino college student in persuasion - Alforque, Kayla; Balagapo, Mary Grace; Deguito, Jastine; Nacional, Raechelle Mae; Nacionales, Joseph P.; Claridad, Norberto (Journal of Language, Literature, Social and Cultural Studies, 2023)
Our eyes have the ability to communicate what we are feeling and how we perceive a situation. This paper assesses the importance of eye contact in persuasion to first-year college students in a qualitative manner. Making eye contact assists students in concentrating on the conversation and reading facial expressions. This can help with comprehension. Improved understanding can also improve communication between two people (Eatough, 2021).  The goal of this study is to learn about students' views toward making eye contact.Using qualitative method with the goal of deepening our understanding of a phenomenon through Interpretative Phenomenological Analysis design. We interviewed 24 1st year students in person and via messenger.The responses of the participants underwent thematic approach of Braun and Clarke (2019). The results revealed that the majority of the participants agree that eye contact makes communication effective. The majority of students believe that eye contact is important in persuading people. They suppose that eye contact increases the credibility and confidence of the speaker. They also consider that eye contact results in effective persuasion. Thorough transcript condensing produced five unique themes:the impact of using eye contact in persuasive communication ,the use of eye contact as a strategy for effective communication, eye contact increases the speaker's credibility in attracting the audience's attention,c omplications due to lack of eye contact, inefficiency of lack of eye contact. Various practical recommendations were further elaborated at the end of the study.